Ciri-ciri keusahawanan dan kecenderungan keusahawanan: Kajian kes dalam kalangan pelajar Kolej Kemahiran Belia Nasional - Nik Zuraini, Mohd Nor (2017)
Generally, entrepreneurial aspects are a hot topic discussed as it is seen as a catalyst for economic development. The government through various agencies has planned and implemented various activities to empower entrepreneurship. One of them is the inculcation of entrepreneurial aspects at the school level. This field can reduce the unemployment rate among school leavers or universities and indirectly overcome socioeconomic problems. There are many factors that motivate person to become an entrepreneur. Among them are entrepreneurial characteristics that must be present in each individual such as creativity, spirit, self confidence and passion. Hence the purpose of this study is to identify and understand the relationships that exist between the characteristics of entrepreneurship with the tendency of entrepreneurship. This study was conducted among students of the National Youth Skills College (KKBN) who enrolled in various major various majors including Electrical Technology, Automotive Technology, Textile Technology, Public Technology, Electronic Technology and others. Questionnaire was distributed to 220 KKBN students, and 150 usable questionnaires were analyzed. The SPSS Version 20 program is used to analyze the research data. There are four (4) hypotheses developed in this study. The Regression test showed two (2) hypotheses were accepeted while other two (2) hypotheses were rejected. The result indicates that entrepreneurial characteristics such as self-confidence and passion are important factors that motivate a student to become a successful entrepreneur among KKBN students. Therefore, the curriculum for TVET students should emphasize on the element of self-confidence and passion to be an entrepreneur if the institution wishes to produce TVET graduates with high entrepreneurial tendencies.